Aberrant transcription factors in the cancers of the pancreas. (November 2022) - Uddin, Md. Hafiz; Al-Hallak, Md. Najeeb; Philip, Philip A.; Chen, Herbert; El-Rayes, Bassel; Azmi, Asfar S.
Abstract: Transcription factors (TFs) are essential for proper activation of gene during the process of organogenesis, differentiation, lineage specificity. Reactivation or dysregulation of TFs regulatory networks could lead to deformation of organs, diseases including various malignancies. Currently, understanding the mechanism of oncogenesis became a necessity for the development of targeted therapeutic strategy for different cancer types. It is evident that many TFs go awry in cancers of the pancreas such as pancreatic ductal adenocarcinoma (PDAC) and pancreatic neuroendocrine neoplasms (PanNENs). These mutated or dysregulated TFs abnormally controls various signaling pathways in PDAC and PanNENs including RTK, PI3K-PTEN-AKT-mTOR, JNK, TGF-β/SMAD, WNT/β-catenin, SHH, NOTCH and VEGF which in turn regulate different hallmarks of cancer. Aberrant regulation of such pathways have been linked to the initiation, progression, metastasis, and resistance in pancreatic cancer. As of today, a number of TFs has been identified as crucial regulators of pancreatic cancer and a handful of them shown to have potential as therapeutic targets in pre-clinical and clinical settings. In this review, we have summarized the current knowledge on the role and therapeutic usefulness of TFs in PDAC and PanNENs.